Spatial variability in the ambient concentrations of polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans across the Middle East - Gevao, Bondi; Martinez-Guijarro, Karell; Kurt-Karakus, Perihan Binnur; Sukhn, Carol; Weber, Roland; Krishnan, Divya; Orif, Mohamed I. (Turkish Natl Committee Air Pollution Res & Control-Tuncap, 2022)
Polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/F) were monitored at 12 sites across four countries (Kuwait, Turkey, Lebanon and, Oman) using validated passive air samplers between January 2018 and December 2018 in an attempt to set up a monitoring network for persistent organic pollutants (POPs) across the Middle East. The highest concentrations of sigma PCDD/F were detected in Oman reflecting the proximity of the site to a steel melting company at Al-Rassil Industrial area (557 fg I-TEQ m-3) and a hospital waste incinerator at Al-Multaga (489 fg I-TEQ m-3). Elevated levels were also measured at all monitoring sites across Kuwait with average concentrations ranging from-150 fg I-TEQ m- 3 at the Shuwaikh site to-250 fg I-TEQ m- 3 at the Salmiya and Abdali sites. Levels of sigma PCDD/F at all other stations in the region were generally lower than 35 fg I-TEQ m- 3. The levels of 1,2,3,4,7,8-HxCDF were frequently a factor of two higher compared to 1,2,3,6,7,8-HxCDF suggesting that an additional source exists which involves the use of elemental chlorine. This study has provided the first reliable measurements of the atmospheric concentrations of PCDD/F in the Middle East providing a baseline for assessing time trends in PCDD/F in the air, one of the core matrices for the effectiveness evaluation under the Stockholm Convention on POPs.
Keywords: Polychlorinateddibenzo-p-dioxins (PCDDs); Polychlorinated dibenzofurans (PCDFs); Passive sampling; Kuwait; Turkey; Lebanon; Oman; Saudi Arabia